Ways for Conceptualization of the Space Area Introduced by the Preposition dans (Based on the French language) (Proceedings of Southern Federal University. Philology, 2021)
Anastassia V. Nikolaenko (Moscow, Russian Federation)The ways for conceptualization of the area of space as a part of the nominal combinations via the French spatial preposition dans as the physical space and the conceptual space are studied in the article; the terms physical space and conceptual space are determined like realities of being and fundamental cultural concepts; the conceptual content of the preposition dans is formulated through the analysis of the spatial constructions. The problem of studying the semantics of the preposition dans in French is still relevant. Large number of works, primarily foreign researchers, who in their works refer to the specifics of cognitive and linguocultural analysis of ways of conceptualizing spaces by French speakers using the preposition dans is the confirmation of the topicality of the article.The perception of space and spatial relationships in each culture occurs in a special way, which is reflected in the language. According to cognitologists, the process of conceptualization depends on a person’s personal perception of the space. The considered cases of various ways of conceptualization allowed us to conclude that the way of conceptualizing the relatum both as a physical and as a conceptual space is explained by the influence of the cognitive context on the perception of a region of space. As the study has shown, it is the cognitive context that creates the basis for the use of lexical categories, with the help of which the interpretation of knowledge about the world occurs in the future.In our case, the interpretation of spatial relations between objects as part of the analyzed structures is facilitated by the cognitive context using the preposition dans.Key words: preposition, space, cognitive context, ways to conceptualization, semantics of French prepositions, cognitive linguistics.DOI 10.18522/1995-0640-2021-2-10-20